Lower Dose of 5 mL of 1% Lidocaine is More Suitable than the Conventional 10 mL for Caudal Block in Transrectal Prostate Biopsy: A Retrospective Cohort Study - Norichika Ueda; Mototaka Sato; Shunsuke Mori; Atsuki Matsukawa; Yuta Oki; Yuma Kujime; Ryoya Mizuno; Hiromu Horitani; Tetsuya Yamamoto; Shota Fukae; Mitsuhiro Yoshinaga; Makoto Matsushita; et al. (Advances in Urology)
Objectives. In Japan, caudal block with 1% lidocaine is commonly used for transrectal prostate biopsy. Although 10 mL of 1% lidocaine is commonly used, the appropriate dosage of 1% lidocaine has not been studied. Our hospital routinely uses two different doses (5 or 10 mL) of 1% lidocaine for caudal block for transrectal prostate biopsy. Herein, we retrospectively evaluated the efficacy and safety of both doses of 1% lidocaine. Methods. This retrospective study included 869 patients who underwent transrectal prostate biopsy with caudal block at our hospital. The amount of 1% lidocaine was determined by the day of the week on which the biopsy was performed, and the patient voluntarily chose the day of the biopsy, unaware of the dose of 1% lidocaine used on that day. Pain, anal sphincter tonus, cancer diagnosis rate, and early complications were compared. Results. In total, 466 and 403 patients received 5 and 10 mL of 1% lidocaine for a caudal block, respectively. After propensity-score matching for patient characteristics, each group contained 395 patients. The pain score, anal sphincter tonus score, or prostate cancer diagnosis rate were not significantly different between the two groups. However, rectal bleeding was significantly more frequent and severe in the 10-mL than the 5-mL group (p=0.018 and p=0.0036, respectively). The incidence of other complications was not significantly different between the groups. Conclusions. Our results suggest that 5 mL of 1% lidocaine may be more suitable than 10 mL for caudal block during transrectal prostate biopsy.